THE INTEGRATION OF EDUTAINMENT AESTHETICS AND SCHOOL ADMINISTRATION - Chamnianpan, Karantarat; Thitavaddhano, Phramaha Yannawat; Tantipalo (Sattaram), Phramaha Werawich; Sitthimethi (Alakul), Phramaha Suchaikon; Kittidhammo (Jarphan), Phramaha Kitphisit; Sirivaddhako, Phrakhrupalad Suravut; Pannipa , Natnicha; Boonpoo, Manassanan (Journal of Educational Review Faculty of Education in MCU, 2024)
This article presented the integration of the principles of aesthetic education with school administration, which was the management of education in a world with high volatility. This was a result of the need to create stable economic and business potential. These things led to adjustment of the entire system in every sector, especially in education. Therefore, educational institution administrators were of paramount importance to the survival of education and were prepared to accommodate continuous changes. As a result, the administration of the educational institution had changed for the better. Including organizing teaching and learning processes that promoted experiences in aesthetic education as physical, emotional, and intellectual development by integrating with the principles of aesthetic education in management with science and art, including: 1) Pleasure: pleasure arising from the mind, 2) Ethics: beauty, goodness, joy, and enjoyment and sincerity, and 3) Function: considering the utility of art. This would bring benefits and be a guideline for the management of educational institutions that having art based on morality and ethics according to the way of life and culture of Thai people who had been nurtured by the teachings of Buddhism and to make the personnel in the educational institution feel joyful and happy with their daily educational duties, which would affect teaching students to have joy and happiness as well as within the family, society, and nation, respectively.